Research Easy Concrete on Base Polymeric Waste (Recycled Aggregate) - Xamrayeva Fariza; Qo’chqorova Farangiz, (European Journal of Life Safety and Stability (2660-9630), 2022)
The purpose of this study was to develop porous concrete with acceptable permeability and strength using recycled aggregate from polymeric waste porosity aggregates. The optimum mix proportions were employed to prepare easy concretes using normal and recycled aggregates. Four different mixes were prepared and tested, which po was used as a coarse aggregate from mass of aggregate 30, 50 and 60%. in 6 consists. Investigated and test results showed, that incorporation coarse aggregate into a mix increase flexural straight to 140% and 145%